Development of an anti-inflammatory diet for first-episode psychosis (FEP): a feasibility study protocol - Kennedy, Leda; Holt, Tiffany; Hunter, Anna; Golshan, Shahrokh; Cadenhead, Kristin; Mirzakhanian, Heline (Frontiers in Nutrition, 2024)
Background: Evidence suggests inflammation plays a role in the pathophysiology of psychosis even in early illness, indicating a potential avenue for anti-inflammatory interventions that simultaneously address high rates of metabolic disease in this population. The aim of this study is to design a novel anti-inflammatory diet intervention (DI) that is feasible to implement in a first-episode psychosis (FEP) population.Methods: Eligible FEP Participants are aged 15-30. The DI is currently being refined through a multi-phase process that includes the recruitment of focus groups that provide insight into feasibility of measures and nutritional education, as well as the implementation of the DI. The phases in the study are the Development Phase, Formative Phase, and the Feasibility Phase.The Development phase has resulted in the creation of a flexible DI for FEP based on existing research on nutritional health and informed by providers. This study has just completed the Formative phase, recruiting eligible participants to join focus groups that gleaned information about dietary habits, preferences, and food environments to further refine the DI.Findings from earlier phases have advised the current Feasibility Phase in which this novel DI is being administered to a small cohort of FEP participants (N=12) to determine acceptability of the DI from a lived experience perspective. Naturalistic changes in inflammatory biomarkers, metabolic health, and symptoms will also be measured.